2021
DOI: 10.1002/ctm2.490
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive and universal approach for embryo testing in patients with different genetic disorders

Abstract: 1. We report a cost-effective, comprehensive, and universal platform for embryo testing in patients with different genetic disorders.2. SNP-based FHLA enables the accurate genetic detection for a wide spectrum of monogenic diseases and chromosome rearrangements in embryos. 3. This proposed strategy may markedly improve the precision of embryo testing and prevent the birth of affected fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…Balanced genomic aberrations, such as balanced translocations and inversions, can cause abnormal phenotypes when the expression or function of critical genes is affected 28. Although most balanced rearrangements carriers show no discernible clinical phenotype, the risk of miscarriage or delivering newborns with chromosomal imbalances is increased in this population because of the unbalanced gametes generated by recombinant chromosomes during meiosis 29 30. Moreover, X-autosome translocation is related to gonadal dysfunction and premature ovarian failure when breakpoints are localised in regions of the X chromosome that are critical for ovarian functions 31.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced genomic aberrations, such as balanced translocations and inversions, can cause abnormal phenotypes when the expression or function of critical genes is affected 28. Although most balanced rearrangements carriers show no discernible clinical phenotype, the risk of miscarriage or delivering newborns with chromosomal imbalances is increased in this population because of the unbalanced gametes generated by recombinant chromosomes during meiosis 29 30. Moreover, X-autosome translocation is related to gonadal dysfunction and premature ovarian failure when breakpoints are localised in regions of the X chromosome that are critical for ovarian functions 31.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 In recent years, our team has illustrated haplotype analysis can also accurately detect balanced and unbalanced chromosome structural rearrangements in human embryos through PGT. 9 The concept that foetal karyotypes can be predicted by inherited parental haplotypes was first introduced for NIPT in this study. The general workflow of our study was illustrated in Figure 1A .…”
Section: Figurementioning
confidence: 99%
“…However, 20 samples with inconclusive calls suggested the biological limitations of OnePGT, which requires additional family members for haplotyping. Zhang et al reported a method based on family haplotype linkage analysis (FHLA) and cnvPartition as the core algorithm to accurately detect a broad spectrum of monogenic diseases, aneuploidy, and chromosome abnormalities in embryos [78] . For 59 embryos, aneuploidies were analyzed using SNP allele frequency and the log R ratio, monogenic disorder and chromosomal rearrangements were detected by haplotypes located within the 2 Mb region covering the targeted genes or breakpoint regions.…”
Section: Pgt-plus As a Comprehensive Pgtmentioning
confidence: 99%